The sweet potatoes new genotypes introduction in Ukraine - Mozgovska A; Ivchenko T; Bashtan N; Miroshnichenko T (Open Journal of Plant Science - Peertechz Publications, 2022)
Aim: Conduct research on the collection of new genotypes of sweet potatoes introduced under growing conditions in the Kharkiv district of Ukraine. Results and discussion: In the conditions in the Kharkiv district of Ukraine, an assessment was made of 13 genotypes of sweet potato a domestic and foreign selection. The genotypes were very different in length of the growing season, biometric parameters of plants, and productivity. The studied genotypes were divided into three ripeness groups. Samples that characterized the three groups - early ripening: V-1, V-6, А-7, В-4; medium ripening: Оr-3, D-2, М-8; late-ripening: B-9, P-11, B-10, J-12, Е-5, Оk-14. A wide range of shapes was obtained along the length of the stem. All genotypes that entered the mid-ripening group formed long, climbing stems. So, plants of the genotype Or-3 formed long stems similar to vines, 214 cm long. The genotypes of the early ripening group were characterized by lengths from 144 cm (V-6) up to 153 cm (А-7). According to the "Quantity of additional shoots" attribute, the variability range was 4-8 cm, and the coefficient of variation was 17%. Significant variation was observed along the length of the internodes (V = 30%). The variability range was 4.39-9.97 cm. According to the "Quantity of leaves" characteristic, the variability range was 40-77 pcs. And the coefficient of variation was 20%. The genotypes of the middle ripening group that had the largest "Quantity of leaves" were 77 pcs./plant (Оr-3) and 71 pcs./plant (D-2). The smallest was 40 pcs./plant (B-10), 42 pcs./plant (B-9), 44 pcs./plant (P-11). The root tubers in genotype V-6 had an oval shape, smooth peel, and pink color. The flesh was a creamy solid color; it was a sample of sweet potato. The shoots were long, climbing, leaves of a dark green color without anthocyanin color, kidney-shaped. The genotype of sweet potato D-2 of Ukrainian selection was a dessert variety. The tubers of the genotype were elliptical, orange with a smooth peel; the flesh was firm and bright orange. The shoots of the plants were very long, very climbing, and light green. The shoots of the leaves were kidney-shaped, light green. The results showed that table genotypes are of greater value for dietary nutrition. Dessert genotypes are conducive to a variety of diets for people with diabetes. A list of genotypes that can be used by people who follow a diet has been provided. Conclusion: In the conditions in the Kharkiv district of Ukraine, 13 introduced genotypes of sweet potato domestic and foreign breeding were evaluated. They already discovered that the genotypes were different in the growing season by biometric parameters of plants and yields. By using clonal selection in vitro culture, two completely new promising genotypes of domestic selection of sweet potatoes V-6 and D-2 were obtained. Tubers of genotype V-6 were oval, skin smooth, and pink. The average weight of one was 351 g. The raw flesh was cream-colored. Long shoots were woven, their length was 144 cm; the leaves were dark green, and kidney-shaped. Another example of a domestic selection of sweet potato D-2 was a dessert type. The root tubers were elliptical and had an orange color with smooth skin. The average weight of the tubers was 410 g. The raw flesh was a solid bright orange color. Shoots were extremely long -198 cm, very creeping, and had a light green color. The leaves were kidney-shaped and light green.